POLA KOMUNIKASI ORANG TUA TUNGGAL DALAM MEMBENTUK KARAKTER ANAK - DINI APRIANI; DINY FITRIAWATI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Communication is very related to daily life. Humans as social beings need communication to convey information or to expedite his social life. Communication patterns are very important and need to be considered to give an idea of ​​communication about a topic that occurs. The first communication that will occur is in the family environment. The family is very very influential in the formation of a person's communication patterns going forward. In the family will not be free from problems, especially if both parents decide to live their lives or get divorced, then the child will have a different parenting. This is the beginning where single parents must be able to form the pattern of children's communication well. The character in a person is usually in line with his behavior. So this research was conducted with a case study method to collect and gain a deep understanding of the individual under study, along with the problems faced in order to be resolved and make the individual self develop better. After conducting research, the results that researchers can get is in educating children which is an obstacle factor for parents in facilitating children's education, namely financial problems, it is necessary to have intense communication done by parents, the success of single parents in educating children by continuing to communicate with children by asking children news, ask about children's activities, and support children's activities. The conclusion is that the speakers succeeded in educating children to become children who have good character and achievement in their schools and in managing their future, the key to good parenting is to continue to have good communication with children and know the children's activities.